Musical expertise is related to neuroplastic changes of multisensory nature within the auditory cortex. (March 2015) - Pantev, Christo; Paraskevopoulos, Evangelos; Kuchenbuch, Anja; Lu, Yao; Herholz, Sibylle C.
Abstract Recent neuroscientific evidence indicates that multisensory integration does not only occur in higher level association areas of the cortex as the hierarchical models of sensory perception assumed, but also in regions traditionally thought of as unisensory, such as the auditory cortex. Nevertheless, it is not known whether expertise‐induced neuroplasticity can alter the multisensory processing that occurs in these low‐level regions. The present study used magnetoencephalography to investigate whether musical training may induce neuroplastic changes of multisensory processing within the human auditory cortex. Magnetoencephalography data of four different experiments were used to demonstrate the effect of long‐term and short‐term musical training on the integration of auditory, somatosensory and visual stimuli in the auditory cortex. The cross‐sectional design of three of the experiments allowed us to infer that long‐term musical training is related to a significantly different way of processing multisensory information within the auditory cortex, whereas the short‐term training design of the fourth experiment allowed us to causally infer that multisensory music reading training affects the multimodal processing within the auditory cortex.